Effects of prostaglandin analog therapy on the ocular surface of glaucoma patients - Michael B Horsley (Dove Medical Press, 2009)
Michael B Horsley, Malik Y KahookRocky Mountain Lions Eye Institute, Department of Ophthalmology, University of Colorado Denver, Aurora, CO, USAPurpose: To quantify changes in tear break-up time (TBUT), corneal staining and ocular surface disease index (OSDI) in glaucoma patients after switching therapy from latanoprost with 0.02% benzalkonium chloride (BAK) to travoprost with sofZia™.Methods: Prospective consecutive case series evaluating patients before and 8 weeks after switching from latanoprost with BAK to travoprost with sofZia™ in patients with baseline TBUT less than 6 seconds.Results: Forty eyes of 20 consecutive patients using latanoprost with BAK were switched to travoprost with sofZia™. Mean TBUT prior to starting travoprost was 2.02 ± 0.71 seconds and increased to 6.34 ± 1.31 seconds 8 weeks after the switch (p < 0.001). Mean inferior corneal staining scores decreased from 2.40 ± 0.87 to 1.38 ± 0.59 (p < 0.001). Mean OSDI scores decreased from 26.31 ± 8.25 to 16.56 ± 6.19 (p < 0.001).Discussion: This report focuses on the status of the ocular surface, as documented by TBUT, corneal staining and OSDI, in patients switched from latanoprost with BAK to travoprost without BAK. The switch resulted in a statistically significant increase in TBUT and decreases in corneal staining and OSDI in patients with low baseline TBUT values.Conclusion: BAK, a common preservative for glaucoma drops, may increase OSD by disrupting the tear film and increasing conjunctival inflammation. In this study, a change from a BAK-preserved prostaglandin analog (PGA) to a non-BAK-preserved PGA resulted in a measurable improvement of TBUT, corneal staining and OSDI. Further studies are needed to better understand the impact of BAK-preserved medications on the ocular surface.Keywords: ocular surface, glaucoma, benzalkonium chloride, prostaglandin analog